STUDY OF MORPHOLOGY (GROSS) AND HISTOPATHOLOGY OF LIGATURE MARK IN HANGING AND LIGATURE STRANGULATION IN HUMAN POPULATION OF AJMER DISTRICT, RAJASTHAN (INDIA) (Journal of Forensic Medicine & Toxicology, 2022)
In humans, hanging is one of the most common method of suicide in the society.The present study was conducted with the basic aim to find out the morphological and hispathological findings in muscle tissue in ligature strangulation three 3 (75%) cases, as compare to hanging 40 (44.4%) . Perifollicular congestion and hemorrhage were the commonest hispathological findings in the thyroid gland in both hanging and ligature strangulation. Follicular hemorrhage was not found in hanging as well as in ligature strangulation..
Keywords: Asphyxial death; hanging; ligature strangulation; morphology; histopathology